Pelatihan Kewirausahaan Bagi Pelaku Usaha Kecil Dan Binaan Koperasi Di Rumah Susun Sederhana Sewa (Rusunawa) Cipinang Besar Selatan - Susita, Dewi; Mardiyati, Umi; Aminah, Hania (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
In an effort to improve empowerment of creative economy, enterpreneurship and management for small business and cooperation is the basis for author to improve the empowerment through training. Training is one of the way to improve the competence of people for generating optimal performance that suitable with the expectation. The study was conducted by using survey method with interview, observation techniques, and questionnaires. The title of this community service activity is Enterpreneurship Training for Small Business and Cultivated Cooperative at Rusunawa Cipinang Besar Selatan. The purpose of this activity is to develop an improve the enterpreneurship as well as improving the management skills of small business and cooperation at Rusunawa Cipinang Besar Selatan. This activity are developing enterpreneurship, market and marketing analysis, business management, partnership, production efficiency, financial management, and business proposal can be useful in developing the business. KATA KUNCI: Enterpreneurship, Management, Small Business and Cooperation